A Study on Wireless Sensor Network, Protocol, Application, Challenges (International Journal of Engineering and Computer Science, 2014)
Wireless Sensor Network is a network in which sensor are deployed in a targeted environment to sense the status of area. The data are collected from sensor, processed, computed and perform the communication process to know about the target environment. The study focuses on the application, protocols, challenges of sensor network which helps for learning process about wireless sensor network and special issue on wireless sensor networks for agriculture. The future work of study is measuring the underground growth and water level monitoring in the plant tapioca (manihot esculenta) using wireless sensor network